2016
DOI: 10.1016/j.vetpar.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a novel oral isoxazoline, sarolaner (Simparica™) in the treatment of naturally occurring flea and tick infestations in dogs presented as veterinary patients in Europe

Abstract: Two randomised, blinded, multi-centered field studies were conducted in Europe to demonstrate the efficacy and safety of three monthly oral doses of sarolaner (Simparica™, Zoetis) administered at a minimum dosage of 2.0mg/kg (range 2-4mg/kg) against natural flea or tick infestation of dogs presented as veterinary patients. In the flea study, the improvement in clinical signs associated with flea allergy dermatitis (FAD) was also investigated. The palatability of the sarolaner chewable tablet formulation was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
5
16
0
Order By: Relevance
“…In the flea study, live flea counts for all species combined were reduced by 97.9% within two weeks after treatment, and this efficacy persisted through the end of the recommended monthly treatment interval with 98.6% reduction 30 days after treatment. These results are comparable to the efficacy reported previously for other orally administered pulicidal medications belonging to both the isoxazoline [13][14][15] and spinosyn class [16] in dogs. This high level of flea control is consistent with the adulticidal activity and breaking of the flea life-cycle through the cessation of flea reproduction that was seen in Simparica Trio ™ laboratory efficacy studies [17].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the flea study, live flea counts for all species combined were reduced by 97.9% within two weeks after treatment, and this efficacy persisted through the end of the recommended monthly treatment interval with 98.6% reduction 30 days after treatment. These results are comparable to the efficacy reported previously for other orally administered pulicidal medications belonging to both the isoxazoline [13][14][15] and spinosyn class [16] in dogs. This high level of flea control is consistent with the adulticidal activity and breaking of the flea life-cycle through the cessation of flea reproduction that was seen in Simparica Trio ™ laboratory efficacy studies [17].…”
Section: Discussionsupporting
confidence: 89%
“…In the tick study, live tick counts for all species combined were reduced by 96.6% within one week after treatment, and this efficacy persisted through the end of the recommended monthly treatment interval with 98.6% reduction 30 days after treatment. Similar studies evaluating oral parasiticides in dogs have demonstrated comparable efficacy against ticks in Europe [13,14,23]. The results of the present field studies are consistent with laboratory studies that confirmed the efficacy of a single oral dose of Simparica Trio ™ against four tick species commonly infesting dogs in Europe.…”
Section: Discussionsupporting
confidence: 87%
“…Sarolaner provided 99.3% (northern study) and 96.7% (southern study) mean efficacy at 14 days after the first treatment and these findings were consistent with previous data reported for field studies conducted in the United States and Europe [ 26 , 27 ]. At the same time point, spinosad provided 94.6 and 97.6% mean efficacy in the northern and southern studies, respectively, which is similar to that previously reported in other studies [ 26 28 ]. The efficacy of sarolaner at the end of the first monthly treatment was ≥ 99.2% compared to the spinosad efficacy of ≥ 89.7%.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that sarolaner is a well‐tolerated and effective option for the treatment of generalized demodicosis in dogs. Additionally it is expected that with the reported high palatability in dogs and with the simple monthly dosing regimen, Simparica ® Chewable Tablets will enhance compliance and help to reduce suboptimal efficacy results …”
Section: Discussionmentioning
confidence: 96%